Preclinical Studies on Mesenchymal Stem Cell-Based Therapy for Growth Plate Cartilage Injury Repair - Rosa Chung; Bruce K. Foster; Cory J. Xian (Hindawi Limited, 2011)
In the last two decades, there has been a strong interest in searching for biological treatments for regeneration of injured growth plate cartilage and prevention of its bony repair. Various means have been tried, including implantation of chondrocytes, mesenchymal stem cell (MSC), together with exogenous growth factor and scaffolds, and gene therapy. However, with the lack of success with chondrocytes, more research has focussed on MSC-based treatments. In addition to circumvent limitations with MSC-based treatments (including cell harvest-associated morbidity, difficulties/time/cost involved in MSC isolation and ex vivo expansion, and potential disease transmission), mobilising endogenous MSCs to the growth plate injury site and enhancing in situ regeneration mechanisms would represent an alternative attractive approach. Further studies are required to investigate the potential particularly in large animal models or clinical setting of the ex vivo MSC approach and the feasibility of the endogenous MSC in situ approach in growth plate regeneration.